Papua Province Regional Government Performance In A Portrait Of Accountability, Transparency and Oversight - Adrin; Junaedy; Haris M Zen; Samsuddin Arfin Dabamona (Faculty of Business and Economics , Universitas Yapis Papua, 2024)
This research aims to obtain empirical evidence of the influence of accountability, transparency, and supervision on the performance of the regional government of Papua Province. This type of research is explanatory research with hypothesis testing. Hypothesis testing is carried out to test the causal relationship between the variables to be studied, namely between the dependent variable in the form of auditor performance and the independent variables (accountability, transparency, and supervision). This research uses primary data obtained directly through field studies using a questionnaire instrument consisting of several statements. The population of this study were employees of Regional Apparatus Organizations in Papua Province. At the same time, the sample was 3 people from each OPD related to regional financial reporting except for the Inspectorate. The author used 15 samples. The research results show that accountability, transparency, and financial transparency influence the performance of the Regional Government of Papua Province. Financial accountability will create better government performance Meanwhile, financial transparency (openness) in the implementation of development can improve local government performance as expected. Meanwhile, effective supervision of regional financial management will improve the performance produced by regional governments.